An Integrated Web-Based Waste Management Platform for Urban Collection Schedulling and Fee Payment Services Pekanbaru City - Ibnu Surya; Juni Nurma Sari; Satria Perdana Arifin; Thesa Nabila Balqis Pardede (ULTIMA InfoSys, 2026)
Waste management has become a global issue, encompassing various challenges such as the separation of organic and inorganic waste, waste collection scheduling, fee collection, and the accumulation of waste at final disposal sites (TPA). In Pekanbaru City, the waste management mechanism involves empowering Waste Collection Agencies (LPS) across 83 sub-districts. LPS is responsible for collecting household waste and transporting it to the TPA, as well as managing the waste collection fees paid by residents. Since the fee management process is still carried out manually, an information system is needed to manage resident data and monitor fee payments effectively. This study developed the SilepasPKU Waste Management Information System using the prototype method, featuring waste collection management and fee management modules. The system was tested through three iterations with LPS UmbanSari users: the first iteration focused on design testing, while the second tested system functionality. Several improvements were made based on user feedback. In the third iteration, all system functionalities operated successfully. Currently, SilepasPKU is being used by LPS UmbanSari in their waste management operations